Feminism and Emotion - Mendus, S. author. aut Link
IX, 197 p.
Keywords: Susan Mendus investigates the significance of love in moral and political philosophy. She argues for a re-interpretation of both enlightenment and feminist thinking, and shows how the former often takes love as central, while the latter draws our attention to human vulnerability and neediness. By combining the insights of enlightenment philosophy and feminist theory, the book aims to provide a new understanding of the role of love in moral and political philosophy.